Pengaruh Investasi Asset Jangka Pendek Dan Aktiva Terhadap Laba Usaha Pada Pt. Taspen (Persero) - Lamuda, Ilyas (Gorontalo Accounting Journal, 2018)
This study was to determine the effect of Short-Term Investments and Assets Assets in generating profits in the company PT. Taspen. The method of analysis used qualitative methods That is explained and analyzed by descriptive data. Quantitative methods to study whether the Short-term investment is profitable or not, can be determined either by the method Accounting Rate Of Return (ARR) That method that measures the level of profit from investments used to gain tersebut.dan the return on investment assets at PT. Taspen. To test the hypothesis then performed calculations using multiple linear regression analysis. Furthermore pengelohan data and hypothesis testing will be assisted by a computer program Softwere SPSS (Statistical Service and Solution product).Research shows that variable Short Term Asset Investments concluded that simultaneous effect relationship is negative and insignificant. But in partial, it provides a significant and positive effect on earnings. Assets Investments variable and not significant positive effect on earnings, but in partial, it provides a significant and positive effect on earnings.